2020
DOI: 10.1093/sysbio/syaa012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Phylogenetics Evaluated Using Novel Evolutionary Simulations

Abstract: Evolutionary inferences require reliable phylogenies. Morphological data have traditionally been analyzed using maximum parsimony, but recent simulation studies have suggested that Bayesian analyses yield more accurate trees. This debate is ongoing, in part, because of ambiguity over modes of morphological evolution and a lack of appropriate models. Here, we investigate phylogenetic methods using two novel simulation models—one in which morphological characters evolve stochastically along lineages and another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 77 publications
1
49
0
Order By: Relevance
“…Despite the oversimplistic substitution model utilized to handle morphological data in probabilistic approaches to phylogenetics (the Mk model [24]), a wave of recent studies have demonstrated that even in such circumstances, probabilistic methods still reach higher accuracy levels than previous criteria (maximum parsimony), with Bayesian inference performing the best regardless of missing data, characters and taxon number (e.g., [23,26,27]). Additionally, the several advances in modeling relaxed clocks in the last decade have made it possible to incorporate a variety of macroevolutionary parameters for the analysis of morphological data in Bayesian phylogenetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the oversimplistic substitution model utilized to handle morphological data in probabilistic approaches to phylogenetics (the Mk model [24]), a wave of recent studies have demonstrated that even in such circumstances, probabilistic methods still reach higher accuracy levels than previous criteria (maximum parsimony), with Bayesian inference performing the best regardless of missing data, characters and taxon number (e.g., [23,26,27]). Additionally, the several advances in modeling relaxed clocks in the last decade have made it possible to incorporate a variety of macroevolutionary parameters for the analysis of morphological data in Bayesian phylogenetics.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several features of morphological datasets make them quite distinct from molecular datasets. Such features include the following: the greater influence of natural selection on the phenotype and its potential impact on developing realistic morphological models [23]; the lack of direct comparability of character states among different characters (as opposed to nucleotides in molecular sequences), thus hampering the development of more complex morphological substitution models [24]; and the much smaller size of the vast majority of morphological datasets compared to molecular sequences. Therefore, it is expected that the impact of model specification on tree topology, divergence times, and evolutionary rates on morphological datasets may vary substantially from molecular datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amynodontidae is closer to the Eggysodontidae-Paraceratheriidae-Rhinocerotidae clade than is Hyracodontidae in the MPT; however, the BIT suggests a closer relationship between the latter two clades. The preference of different topologies generated by the parsimony and Bayesian analysis for morphological data are ongoing debate 67,68 , and it seems that both have advantages and disadvantages for morphological data 69,70 . The parsimony method only provides a point estimate (the MPTs) while Bayesian inference averages over the uncertainties of the topologies by summarizing a majorityrule consensus tree.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the taxa or clade contradictory in both methods indicate that the data might not contain enough information to draw firm conclusions about their relationships 71 . With more fossils and more complete data added in the matrix in combination with improvements of algorithms and parameters 70,72,73 , two methods probably converge to more compatible results.…”
Section: Discussionmentioning
confidence: 99%